2008
DOI: 10.1111/j.1346-8138.2008.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Case of skin injuries due to stings by crown‐of‐thorns starfish (Acanthaster planci)

Abstract: A case of skin injuries due to stings by crown-of-thorns starfish, Acanthaster planci, in a 53-year-old Okinawan woman is reported. She went to a beach to gather shellfish on 8 April 2001 and fell to the ground with her left palm on a crown-of-thorns starfish that happened to be close to her. She hurried to the emergency section of our hospital. An emergency doctor sterilized the wound and administered an antibiotic, an analgesic agent and an injection of a tetanus antitoxin. He tried to remove the remaining s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…A previous study also reported that the venom from A. planci spines is unstable in acidic (pH < 3) or alkaline (pH > 10) environments [1]. Our results corroborated the instability of ASV hemolysis in an alkaline environment.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A previous study also reported that the venom from A. planci spines is unstable in acidic (pH < 3) or alkaline (pH > 10) environments [1]. Our results corroborated the instability of ASV hemolysis in an alkaline environment.…”
Section: Discussionsupporting
confidence: 89%
“…Our results showed that the venom from the spines of A. palnci from Taiwan exhibits strong hemolytic activity. The venom was characterized as a protein and such results are similar to previous reports [1-3]. …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The accidental sting by venomous crownof-thorns starfish can result in symptoms of illness such as an extremely painful wound, with redness and swelling occurring immediately (Shiomi et al, 1985). The symptoms of nausea and protracted vomiting may also occur (Sato et al, 2008).…”
Section: Introductionmentioning
confidence: 99%